Pemekaran Daerah dan Krisis Lingkungan: Suatu Telaah Kritis Atas Kerusakan Alam - Leo Agustino; Muhammad Agus Yusoff (Magister Administrasi Publik, 2009)
This paper discusses decentralization and its impact on the environment. It states that decentralization has emerged environmental degradation. Since decentralization took place, illegal logging, illegal mining and many other natural resources exploitation had occurred worse than ever before. Local elites (political, bureaucracies, and industries) together with the local community engage to exploit the natural resources for increase their prosperity. This is pushed for four reason: 1) legacy from the New Order period that earn money though easy way; 2) return for their campaign fund for the elected official such governor or regent; 3) patron client relationship between the elected official and their supporters which is the former give that material resources (licenses, contract, etc) and the later give their loyalties; and 4) revenge for poverty that the have ever around as marginalized local people in New Order period. To figure out this problem, the writers argue for four alternatives: 1) enhance the legal consciousness and raise the awareness for preserve the environment; 2) increase in controlling mechanism and give strict sanction for disobediences; and involve the third parties (NGO, both local and international) for overcoming the environmental crisis.